THE RELATIONSHIP OF PERSONAL MATURITY OF THE ADOPTIVE PARENTS AND THE PROCESS OF SOCIALIZATIONAND IDENTIFICATION OF PRESCHOOL CHILDREN - A N Pronina; S V Markova (Peoples' Friendship University of Russia (RUDN University), 2015)
The article is devoted to the topic of the development of children from orphanage in a foster home, showing the importance of personal maturity of the adoptive parents. The authors present the results of a study showing that there is a relationship between the individual criteria of personal maturity of the adoptive parents and the process of socialization and individualization of the children from orphanage.